Adult height and cancer mortality: The Asia Pacific Cohort Studies Collaboration - Batty, G. David (2009)
BACKGROUND: The observation that taller people experience an increased risk of selected cancers is largely restricted to Caucasian cohorts. These associations may plausibly differ in Asian populations. For the first time, we make direct comparison of the associations between height and a series of malignancies in Australasian (Caucasian) and Asian populations. METHODS: Analyses were based on the Asia Pacific Cohort Studies Collaboration of 506, 648 male and female study participants (408,381 Asia, 98267 Australasia) drawn from 38 population-based cohort studies. Cox proportional hazards regression was used to estimate the relationship between height and cancer rates. RESULTS: A total of 3,272,600 person years of follow-up gave rise to 7497 cancer deaths (5232 in men, 2265 in women). After multiple adjustments and left censoring, taller individuals experienced increased rates of carcinoma of the intestine (men and women); all cancers, liver, lung, breast, ‘other’ malignancies (all women); and prostate and bladder (men). No consistent regional (Asia vs. Australasia) or sex-differences were observed. CONCLUSIONS: In the present study, taller men and women had an elevated risk of selected malignancies. These associations did not differ appreciably between Asian and Caucasian populations.